(untitled) (Bangladesh Journal of Agricultural Research, 2018)
Integrated management of Fusarium wilt of gladiolus was studied at Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during 2011-2013 following RCB design with four replications. Seven treatment such as (1) Corm treated with Bavistin @ 0.1% for 15 minutes, (2) Corm treated with hot water @ 54oc for 5 minutes, (3) Corm treated with hot water @ 52oc for 10 minutes, (4) Poultry refuse @ 5t/ha, (5) Mustard oil cake @ 600 kg/ha, (6) Bio-pesticide @ 64kg/ha, (7) Bavistin @ 0.1% as soil drenching were evaluated in nine different combinations against the Fusarium wilt of gladiolus (Fusarium oxysporum f. sp. gladioli) under naturally infested field condition. Corm treated with Bavistin (0.1%) for 15 minutes + Poultry refuse @ 5t/ha in soil application 25 days before corm sowing + Bavistin @ 0.1% as soil drenching at 45 days after corm sowing gave best integrated management option for reducing Fusarium wilt of gladiolus and thereby resulting maximum germination, spike length, rachis length, florets spike-1, flower sticks, corm and comel yield. Besides, integration of Bavistin (0.1%) as corm treatment for 15 minutes + Mustard oil cake @ 600 kg/ha in soil application 25 days before corm sowing + Bavistin (0.1%) as soil drenching at 45 days after corm sowing was also better option for combating Fusarium wilt of gladiolus. The alternate option was integration of Bavistin (0.1%) as corm treatment for 15 minutes + Bio-pesticide in soil application 7 days before corm sowing + Bavistin (0.1%) as soil drenching at 45 days after corm sowing was effective against the disease incidence as well as better spike length, rachis length, florets spike-1, flower sticks, corm and cormel yield. Bangladesh J. Agril. Res. 43(1): 13-23, March 2018